Configuration development on the platform 1C for enterprise automation - Liakhov, O. L.; Dmytrenko, T. A.; Tverdokhlib, A. O.; Derkach, T. M.; Dmytrenko, A. O. (Математичні машини і системи, 2015)
In this paper, the results of configuration development on the platform 1C for limited liability companies were presented. The object of study is the development process configuration platform 1C. The purpose of the study is the technological platform “1C: Enterprise”. The tasks included analyzing the technological platform “1C: Enterprise”, comparing the most popular ERP-systems, configurator development on the platform 1C. Such research methods as structured programming techniques and methods of evidence-based programming for the systematic analysis of the correctness of algorithms and algorithmic development programs without errors were used in the paper.